SEMANTIC REVIEW ON THE REFORMULATION AS THE FORM OF CLARIFICATION IN APPOSITIONAL CONSTRUCTIONS - Hero Gunawan; Puspita Sari (University of Kuningan, 2023)
This research-based article discusses appositives containing reformulation which is very important in the context of meaning particularly in the form of clarification to the anchor as the antecedent. This reformulation is viewed from the two aspects, i.e., semantic equivalence and coreference. Therefore, this research serves two aims: 1) to elucidate the forms of clarification provided by reformulation as semantic equivalence that makes anchors more comprehensible, and 2) to elaborate whether reformulation and its anchor are coreferential in the appositional constructions. The data sources are taken from English printed media within three levels of distributional coverage, i.e., national, regional and international coverage. The data are analysed through employing the method of qualitative research, that is, the method presenting descriptive data, both written and oral data. To analyse such descriptive data, the distributional method of analysis with the two techniques is used, namely, extracting techniques, and inserting techniques. The results of this research uncover that 1) the forms of clarification provided by the reformulation cover: a) metaphorical expression, b) factual knowledge, c) expression of revision, d) simplified expression, e) short forms (acronyms), f) emphasis through negative reformulation, and g) equivalence in other language; and 1) not all reformulations have coreferences. All of the reformulation forms are given to make the anchor more comprehensible.